Death and Other Endings - Garcia, Moises S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 2 (2000): Indigenous Peoples, 2009)
A book review of Kristina Gaerlan and Mara Stankovitch's "Warlords and Ulama"